The relationship between intellectual capital and financial performance an analysis of some selected Malaysian public listed companies / Siti Nur Fathiah Basri - Basri, Siti Nur Fathiah Basri (2019)
The objective of this study is to determine the relationship between components of Intellectual Capital (IC) towards Return on Asset (ROA) of the company. IC is comprises of three components which is Human Capital (HC), Structural Capital (SC), and Capital Employed (CA). The data is obtained from annual report of each company and from previous study. In this study, the data is being collected from year 1999 until 2018 from fifteen (15) companies some selected Malaysian Public Listed Companies. Financial statements is the data being extracted for the purpose of this study. The reason these fifteen companies is being chosen because it is a public listed company and they are using a high technology for their production. This study are using Value Added Intellectual Capital (VAIC) method in order to determine the relationship between Intellectual Capital components and Return on Asset of the company. Besides that, tests such as Descriptive Analysis, Pearson Correlation and Regression Analysis was used to determine the relationship between IC components and ROA of the company. As for the findings, VAHU seems to be the most significant compare with VACA, STVA and VAIC. This shows that companies are depending highly towards VAHU in order for them to increase their performance. More than that, STVA and VACA is not significant, meaning that the company are not able to utilize the component efficiently, Overall, the company need to applied intellectual capital components for their company in order to increase competitive advantage and financial performances.